PENGELOLAAN ADMINISTRASI KEUANGAN PADA PUSAT KESEHATAN MASYARAKAT (PUSKESMAS) SUWAWA TENGAH KABUPATEN BONE BOLANGO - Sakbir (STISIPOL Mujahidin Buol, 2024)
This research aims to determine the financial administration management at the Central Suwawa Community Health Center. The research method uses a qualitative type. The research results show that financial administration management at the Central Suwawa Health Center is optimal. This can be seen from the needs-based planning aspect and the programs implemented in the current year and also in the following year. From the recording aspect, it has been carried out well, where every activity or financial transaction is recorded in the books and stored in computer files. In the reporting aspect, it was carried out well, namely that financial reporting activities used SIPD and SIMDA. Meanwhile, another indicator that is considered not yet optimal is the control indicator, this can be seen from the frequent discrepancies between financial planning and implementation which results in less than optimal budget use.